2014
DOI: 10.1021/jp502971j
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time-Monitoring of the Synthesis of β-NaYF4:17% Yb,3% Er Nanocrystals Using NIR-to-Visible Upconversion Luminescence

Abstract: In situ real-time monitoring of upconversion emission is applied to study the reaction mechanism for the synthesis of β-NaYF4:17% Yb,3% Er nanoparticles in oleic acid and octadecene via the heat-up method. Transmission electron microscopy is used to correlate the spectroscopic signature of the reaction mixture with its composition. The power of real-time spectroscopic monitoring to precisely time the duration of the various stages of the reaction, and to accurately identify the transitions between those stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 54 publications
5
49
0
Order By: Relevance
“…188,[212][213][214][215] Later, Suter et al were the first who exploited the intrinsic UCL properties of UCNPs which enables real-time monitoring of the particle growth. 216 Their findings support a thermodynamically driven dissolution/recrystallization process. They even proposed a four stage process for the growth of β-phase UCNPs, which is supported by our results.. 159,217 As the most efficient UCNPs are mainly synthesized in organic solvents, the applicability is limited as the particles are stabilized by hydrophobic ligands.…”
Section: Synthesis Of Upconversion Nanoparticlesmentioning
confidence: 78%
“…188,[212][213][214][215] Later, Suter et al were the first who exploited the intrinsic UCL properties of UCNPs which enables real-time monitoring of the particle growth. 216 Their findings support a thermodynamically driven dissolution/recrystallization process. They even proposed a four stage process for the growth of β-phase UCNPs, which is supported by our results.. 159,217 As the most efficient UCNPs are mainly synthesized in organic solvents, the applicability is limited as the particles are stabilized by hydrophobic ligands.…”
Section: Synthesis Of Upconversion Nanoparticlesmentioning
confidence: 78%
“…TRANES could also be a great tool for monitoring the phase composition of UCNP in situ during synthesis. 84,85…”
Section: Resultsmentioning
confidence: 99%
“…Our results strongly suggested that the -phase nanocrystals may also grow by the coalescence process beside the Ostwald ripening phenomenon that was reported in the literature. 26,30,32 Surprisingly, despite the high temperature (310 °C) and homogeneous heat transfer of the microtube 879 , one could not observe any hexagonal β-phase with HRTEM before 90 min of heating. This was probably related to the slow change in shape and size of the α-phase nanocrystals.…”
Section: Growth Of Nanocrystals Into Microtube 879 At Higher Temperature (310 °C) For Various Heat Treatment Timesmentioning
confidence: 93%
“…23,24 Significant efforts have also been invested in the characterization of their growth and phase transition mechanism. [25][26][27][28][29][30][31][32] Suter et al have investigated the growth of nanocrystals and the transition from cubic α-phase to hexagonal β-phase in real-time by monitoring their NIR-to-visible upconversion emission. 30 They have defined four stages related to the evolution of NaYF 4 nanocrystals during the heat treatment step, in which the longest period of time is between the initial formation of the small cubic α-phase nanocrystals and the start of the phase transition that was called relative stasis phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation